Exploring the Sources of Self-Efficacy Perceived by High-Achieving Students in Speaking Performance - Muhammad Hafid Chusaini (Arden Jaya Publisher, 2026)
This study explores the sources of self-efficacy in English-speaking performance among high-achieving EFL students. A qualitative case study design was employed involving five eleventh-grade students from a public senior high school in Surabaya, Indonesia. Data were collected through semi-structured interviews to obtain in-depth insights into students’ lived experiences in speaking English. The data were analyzed using thematic analysis to identify patterns related to four sources of self-efficacy: enactive mastery experience, vicarious experience, social persuasion, and physiological and affective states. The findings show that all four sources contribute to the development of self-efficacy, but social persuasion emerges as the most dominant factor. Teacher feedback and parental support significantly strengthen students’ confidence in speaking English. Vicarious experience functions in two ways, as it can increase motivation when observing successful peers, but also trigger self-doubt in competitive environments. Enactive mastery experience is strongly shaped by preparation habits and perfectionist tendencies, which may weaken confidence despite high academic achievement. Physiological and affective states such as anxiety and nervousness are commonly experienced but managed through coping strategies and cognitive regulation. The study concludes that self-efficacy among high-achieving students is not only determined by personal achievement but is strongly influenced by social and environmental factors that shape confidence in speaking performance.